Simulation of Rarefied Gas Flows in Microchannels. (2017) - Kurkin, Eugene I.; Samsonov, Vladimir N.; Shakhov, Valentin G.
Abstract: In this work the rarefied gas flows in microchannels is investigated. With low pressure owing to low gas density the gas slippage affetcting the channel walls is observed. The task of sliding flow on initial segments of flat (two-dimensional) channel of uniform cross section is solved. Intercomparison of two calculation methods is carried out. The analytical method is based on approximate approach developed by S. M. Targ. The small channel extension does not always allow application of the formulas of calculation of hydraulic resistance, received for long (theoretically infinitely long) channels. The physics of process are also answered, more by development of flow on the so-called initial segment, when the flow characteristics change not only on a cross section of the channel, but also along its length. As a result of the reasonable simplification of the initial tasks it was possible to receive the simple formulas for practical calculations of the main hydrodynamic characteristics and the value of velocity and pressure of flow on channel length. The numerical solution of the task is carried out with the control-volume method in an ANSYS CFX system with use of structured computational mesh, constructed in ANSYS ICEM CFD. The task is solved in a flat statement: cells are located in one layer and on the sidewalls of layer the symmetry conditions are set. The closed system of the Navier-Stokes equations is solved. The laminar flow mode taking into account a slipping condition on wall of "Finite Slip Wall" is considered. Calculations are carried out for Knudsen numbers from 0 to 0, 1 with step in 0, 02. The intercomparison of the modeling results obtained by analytical and numerical methods showed good agreement.